Keterampilan Berbahasa Inggris Melalui Pengenalan Connected Speech untuk Guru-Guru SMAN 16 Batam: English Language Skills Through Connected Speech Introduction for Teachers at SMAN 16 Batam - Ambalegin, Ambalegin; Afriana, Afriana; Irawan, Nafdi; Tewarat, Sipri Hanus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Mastering English for teachers can increase their competency in this digital era. Teachers who speak English achieve their selling point in communication, gain access to global references and the latest educational technology, and broaden their professional mindsets. This training trained the participants to understand non-native speakers of English, and speak English like non-native speakers by providing connected speech which contains linking, assimilation, elision, silent letters, and intrusive [j] dan [w] as the topic. This training, which 55 teachers attended, was held at SMAN 16 Batam on 17, 23, and 31 January 2025. This training applied a service-learning method with models of lectures, discussions, and practice. The results showed an increase in ability of 71%, when initially only two participants could pronounce them before training. The planned and sustainable programmes will provide successful English language training. Having the ability to speak English is not only useful for teachers but also for the school and the students being taught.